Invasive Tree Pests Devastate Ecosystems—A Proposed New Response Framework - Bonello, Pierluigi; Campbell, Faith T.; Cipollini, Don; Conrad, Anna O.; Farinas, Coralie; Gandhi, Kamal J. K.; Hain, Fred P.; Parry, Dylan; Showalter, David N.; Villari, Caterina; Wallin, Kimberly F. (Frontiers in Forests and Global Change, 2020)
• Maintenance and restoration of forest ecosystems will be key to achieving necessary carbon sequestration goals, protecting biodiversity, and supporting healthy economies and societies. • Forest ecosystems are increasingly threatened by non-native forest insects and phytopathogens. • A portion of these pests are able to overcome prevention and containment efforts and become established in naïve ecosystems. • Once established these pests pose a long-term large-scale threat to forest ecosystems, which current policy and response frameworks are poorly equipped to address. • We propose the creation of a federal Center for Forest Pest Control and Prevention to implement end-to-end responses to forest pest invasions using an ecologically-informed framework that fully integrates host tree resistance development and deployment.